Prognostic significance of stress hyperglycemia ratio in patients with type 2 diabetes mellitus and acute coronary syndromes - Xiaoteng Ma; Huijun Chu; Yan Sun; Yujing Cheng; Dai Zhang; Lixia Yang; Zhijian Wang; Xiaoli Liu; Yujie Zhou (Thrombosis Journal)
Abstract Background Prognostic significance of stress hyperglycemia ratio (SHR) has not been well studied in patients with type 2 diabetes mellitus (T2DM) and acute coronary syndromes (ACS). Methods We prospectively measured admission fasting blood glucose (AFBG) and glycated hemoglobin A1c (HbA1c), and retrospectively calculated the stress hyperglycemia ratio (SHR, = AFBG/[1.59 × HbA1c (%) − 2.59]) in 791 patients with T2DM and ACS undergoing percutaneous coronary intervention (PCI). The primary endpoint was defined as major adverse cardiovascular and cerebrovascular events (MACCE), including all-cause mortality, non-fatal stroke, non-fatal myocardial infarction, and unplanned repeat coronary revascularization. Results The mean age of the study population was 61 ± 10 years, and 72.8% were male. Over a median follow-up of 927 days, 194 patients developed at least one primary endpoint event. The follow-up incidence of MACCE increased in parallel with SHR tertiles (15.6%, 21.9%, and 36.1%, respectively; P for trend < 0.001). The Cox proportional hazards regression analysis adjusted for multiple confounding factors showed hazard ratios for MACCE of 1.525 (95% CI: 1.009–2.305; P = 0.045) for the middle tertile and 2.525 (95% CI: 1.729–3.687; P < 0.001) for the highest tertile of SHR, with the lowest tertile as the reference. The addition of SHR to the baseline reference prediction model improved model predictive performance markedly (C-statistic: increased from 0.704 to 0.721; cNRI: 0.176 [95% CI: 0.063–0.282], P = 0.002; IDI: 0.030 [95% CI: 0.009–0.063], P = 0.002). Conclusion SHR was independently and significantly associated with adverse cardiovascular outcomes in T2DM and ACS patients who underwent PCI, and had an incremental effect on the predictive ability of the baseline reference prediction model.